COVID-19 and public policy - Chatterji, Manas; Bhattacharya, Rabindra Chandra; Chakrabarty, Shambu Prasad (Contributions to conflict management, peace economics and development ;, 2025)
The COVID-19 pandemic caused widespread disruption and rapid change, impacting public policy with unprecedented impact globally, nationally, regionally, and locally. All facets and groups within society were affected, and the aftermath of this is still being felt. Stemming from the international meeting, "Disaster Management: Global Pandemic and Its Impact" held in Binghamton University, New York on Jan. 23-25, 2023, this volume of the Contributions to Conflict Management, Peace, Economics and Development series features an international authorship discussing a wide array of key topics. Shining light on the issues emphasized during the COVID-19 pandemic, from the European Union, energy, and the environment, dietary factors and sleep, crime, leadership, online dispute resolution, to risk perception, biopower and trust, COVID-19 and Public Policy comprehensively covers age, gender, geographical locations, and more. COVID-19 and Public Policy is of great value to policymakers and researchers internationally navigating the post-COVID-19 world.